An Empirical Study on the Relationship between Language Proficiency and Economic Income of Chinese and Vietnamese Border Residents: A Case Study of Dongxing City, Guangxi Province (JOURNAL OF ADVANCES IN LINGUISTICS, 2020)
Based on the full sample survey of border residents in Dongxing City, Guangxi, this paper uses language economics theory and data analysis methods to analyze the relationship between language proficiency and income of border residents in Dongxing City, Guangxi. The conclusions of the study include: multilingual ability can enhance residents' self-employment ability, obtain more employment opportunities and stable income sources, and have a positive correlation with their annual income. Putonghua popularization is an effective measure to promote poverty alleviation in border areas; Government departments should optimize and improve local industrial policies and promote the promotion and protection of traditional cultures of ethnic minorities while giving full play to the positive economic and social benefits of Putonghua popularization and cultivating new economic drivers.